JavaServer pages pocket reference - Bergsten, Hans (Java series (O'Reilly & Associates), 2001)
JavaServer Pages (JSP) is harmonizing how web designers and programmers create dynamic web pages. The reason for this is simple: JSP capitalizes on the power of Java servlets to create effective, reusable web applications. JSP allows you to develop robust, powerful web content, and the best part is that you're not required to be a hard-core Java programmer. JavaServer Pages Pocket Reference is the perfect companion volume to O'Reilly's best-selling JavaServer Pages, also by Hans Bergsten. This book provides detailed coverage of JSP syntax and processing, directive elements, standard action elements, scripting elements, implicit objects, custom actions, tag library description creation, and WARs.